A tale of two parasites: a glimpse into the RNA methylome of patient-derived Plasmodium falciparum and Plasmodium vivax isolates - Priyanka Roy; Sukriti Gujarati; Pallavi Gupta; Ishaan Gupta; Tanmaya Mahapatra; Dinesh Gupta; Sanjay Kumar Kochar; Dhanpat Kumar Kochar; Ashis Das (Malaria Journal)
Abstract Background Understanding the molecular mechanisms of the malarial parasites in hosts is crucial for developing effective treatments. Epitranscriptomic research on pathogens has unveiled the significance of RNA methylation in gene regulation and pathogenesis. This is the first report investigating methylation signatures and alternative splicing events using Nanopore Direct RNA Sequencing to single-base resolution in Plasmodium falciparum and Plasmodium vivax clinical isolates with hepatic dysfunction complications. Methods Direct RNA Sequencing using Nanopore from clinical isolates of P. falciparum and P. vivax showing hepatic dysfunction manifestation was performed. Subsequently, transcriptome reconstruction using FLAIR and transcript classification using SQANTI3, followed by methylation detection using CHEUI and m6Anet to identify N6-methyladenosine (m6A) and 5-methylcytosine (m5C) methylation signatures, was done. The alternative splicing events from both the datasets were documented. Results The reference genome of Plasmodium reports > 5000 genes out of which ~ 50% was identified as expressed in the two sequenced isolates, including novel isoforms and intergenic transcripts, highlighting extensive transcriptome diversity. The distinct RNA methylation profiles of m6A and m5C from the expressed transcripts were observed in sense, Natural Antisense Transcripts (NATs) and intergenic categories hinting at species-specific regulatory mechanisms. Dual modification events were observed in a significant number of transcripts in both the parasites. Modified transcripts originating from apicoplast and mitochondrial genomes have also been detected. These modifications are unevenly present in the annotated regions of the mRNA, potentially influencing mRNA export and translation. Several splicing events were observed, with alternative 3′ and 5′ end splicing predominating in the datasets suggesting differences in translational kinetics and possible protein characteristics in these disease conditions. Conclusion The data shows the presence of modified sense, NATs and alternatively spliced transcripts. These phenomena together suggest the presence of multiple regulatory layers which decides the post-translational proteome of the parasites in particular disease conditions. Studies like these will help to decipher the post-translational environments of malaria parasites in vivo and elucidate their inherent proteome plasticity, thus allowing the conceptualization of novel strategies for interventions.